ASSESSMENT OF PESTICIDE USAGE FOR VEGETABLE CULTIVATION IN NUWARA ELIYA DISTRICT - Dilhani, R.A.D.I.; Chaminda, K.G.S.; Pathirana, K.P.S.R.; Marapana, R.A.U.J.; Jayasinghe, J.M.J.K.; Navarathna, S.B. (PROCEEDINGS - IRCHSS 2015, 2015)
Attached
Keywords: farmer behavior; pesticides; vegetable cultivation; water sources